Labour regulations and growth of manufacturing and employment in India: Balancing protection and flexibility - Anwarul Hoda; Durgesh K. Rai (Indian Council for Research on International Economic Relations (ICRIER), 2015)
The factors responsible for the lacklustre performance India's manufacturing are well identified in contemporary literature. The important ones are absence of world class infrastructure, complex system of internal taxation, an unpredictable taxation environment, and regulations relating to land and labour. This paper explores the difficulties in the area of labour regulations, focusing on the enactments and provisions that inhibit flexibility of manufacturing enterprises in adapting to swift changes in the conditions of competition in international markets. The regulations in India that impinge on labour flexibility and the related practices are analysed and compared with those prevailing in major developed and emerging countries, before coming to a conclusion on the changes that are needed in the country. The aspects that come in for detailed scrutiny are collective dismissal, fixed term contracts, contract labour, trade unions and unemployment insurance. Although the main aim of the authors is to obtain greater flexibility, the recommendations are designed to ensure that a balance is maintained between labour market flexibility and protection of labour.
Keywords: J21; J51; J52; J53; L60; 330; Labour regulations; Labour market flexibility; Manufacturing; Employment; India